Unusual causes of calf swelling–1. Unusual presentation of a tibial artery false aneurysm. Issue 742 (August 1987) - Rowe, P.; Taylor, P.; Franklin, A.; McColl, I.; Missen, A.; Spencer, J.
Abstract : Peripheral aneurysms of the leg are rare, and nearly always involve the popliteal artery. We describe the unusual presentation of a swollen leg caused by a large false aneurysm of a branch of the posterior tibial artery. This developed in the absence of either a history of trauma, local infection or infective endocarditis.